High-toughness particle-reinforced dual-phase magnesium-lithium alloy as well as preparation process and application thereof

By adding micro- and nano-ceramic particles to the dual-phase magnesium-lithium alloy and optimizing the composite deformation process to refine the grains and improve the dislocation strengthening effect, the problem of difficulty in balancing plasticity and strength of the dual-phase magnesium-lithium alloy is solved, and strong plasticity is achieved Collaborative improvement to meet the performance requirements in the aerospace field.

CN119351838APending Publication Date: 2025-01-24DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411465293.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Dual-phase magnesium lithium alloys are difficult to take into account the mechanical properties such as plasticity, strength and elongation. The strength increase of the prior art is not obvious when improving plasticity, or the plasticity decreases when increasing strength.

Method used

On the basis of refining the grains of rare earth and CA elements, add micro and nano ceramic particles to further refine the solidarity tissue, improve the effect of enhancing the bits, weaken the plastic loss caused by traditional deformation, and achieve strong plasticity by optimizing the composite deformation process parameters to achieve strong plasticity. Coordinated improvement.

Benefits of technology

The dual-phase magnesium-lithium alloy has achieved synergistic improvement in tensile strength, yield strength and elongation. The tensile strength is 320-380MPa, the yield strength is 300-360MPa, and the elongation is 8%-15%, which meets the requirements of military industry and aviation. Performance requirements in the aerospace sector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351838A_ABST
    Figure CN119351838A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-toughness particle-reinforced dual-phase magnesium-lithium alloy as well as a preparation process and application thereof. The high-strength and high-toughness particle-reinforced dual-phase magnesium-lithium alloy comprises the following components in percentage by weight: 6 to 10 percent of Li, 1 to 6 percent of Al, 1 to 6 percent of Zn, 0.2 to 1 percent of Gd, 0.1 to 1 percent of Y, 0.1 to 1 percent of Ca and 0.05 to 1 percent of ceramic particles. According to the magnesium-lithium alloy, micro and nano ceramic particles are added on the basis of rare earth and Ca refined grains, the solidification structure is refined, and the dislocation strengthening effect is improved; meanwhile, the composite deformation process parameters are optimized, the hard rare earth phase and the nanometer strengthening phase are regulated and controlled, the dislocation density and the texture strength are enhanced, the strength and plasticity of the double-phase magnesium-lithium alloy are greatly improved, and the performance indexes of structural parts in the military industry and the aerospace field can be met. The method is simple in preparation process, short in flow and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to magnesium-lithium alloy technology, and in particular to a high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy, and a preparation process and application thereof. Background Art

[0002] Magnesium-lithium alloy is currently the lightest metal structural material, known as ultra-light alloy, with a density of only 1.35-1.65g / cm 3 , which has the characteristics of high specific strength and high specific stiffness, high impact toughness, good electromagnetic shielding performance, etc. Compared with magnesium alloys of other systems, it also has the advantage of easy plastic processing. In addition, magnesium-lithium alloys have a rich structural system, and different structural systems have great differences in performance and deformation capacity. The plastic deformation ability of single-phase α-Mg magnesium-lithium alloy is poor, and the Li content is low and the density is high; although the β-Li magnesium-lithium alloy has strong plastic deformation ability and low density, the high price of Li causes its manufacturing cost to increase sharply, and the excessive Li content leads to strong plastic instability. Therefore, strengthening the research on dual-phase magnesium-lithium alloys and developing new compositions and deformation processes to obtain magnesium-lithium alloys with good strength and plasticity matching are important tasks and development trends in the current research field of new metal materials.

[0003] Grain refinement is an important means of microstructure regulation during the preparation of magnesium-lithium alloys, and it is also an effective way to improve the mechanical properties of magnesium-lithium alloys. Rare earth elements precipitate on grain boundaries to form dispersed hard second phases, hinder dislocation movement and refine grains. It can serve as the core of heterogeneous nucleation or be enriched near grain boundaries to inhibit grain growth. The literature Transactions of Nonferrous Metals Society of China, 2022, 32 (8): 2494-2509 achieves grain refinement in dual-phase Mg-Li-Al-Zn alloys by regulating the rare earth element Gd, so that the elongation of the cast dual-phase Mg-Li-Al-Zn alloy is increased to 42%, but the strength is only 190MPa. The addition of rare earth elements greatly improves plasticity, but the strength improvement is not obvious. Grain refining elements such as Ca and Zr have been proven to be able to significantly refine the structure of magnesium-lithium alloys. Patent CN 118207455 A effectively refines the cast grains by adding different amounts of Ca to the dual-phase Mg-Li-Al-Zn alloy, increasing the strength of the cast alloy from 160MPa to 210MPa, but the elongation decreases by 20-40%, and the synergistic improvement of strength and plasticity is not achieved. Ceramic particles can act as particles for heterogeneous nucleation or be enriched near grain boundaries to inhibit grain growth. The document Composites Science and Technology, 2007, 67(9): 1965-73 adds SiC particles to the dual-phase magnesium-lithium alloy and finds that the addition of SiC ceramic particles has a significant refining effect, but the distribution of SiC particles in the matrix is ​​uneven and accompanied by obvious agglomeration. Patent CN 111304506B successfully prepares TiB by powder metallurgy. 2 The particle-reinforced dual-phase Mg-Li-Al-Zn-Y matrix composite material was deformed by a single forging, extrusion or rolling process, and the tensile strength was up to 374 MPa, but the plasticity was only 1.2%. It is difficult to achieve a synergistic improvement in strength and plasticity with a single deformation process. Summary of the invention

[0004] The purpose of the present invention is to propose a high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy to address the problem that the current dual-phase magnesium-lithium alloy cannot have both plasticity, strength, elongation and other mechanical properties. The alloy, on the basis of rare earth and Ca element grain refinement, adds micro- and nano-ceramic particles to further refine the solidification structure, enhance the dislocation strengthening effect, greatly reduce the plasticity loss caused by traditional deformation, achieve a synergistic improvement of strength and plasticity, and has excellent plasticity, strength and elongation.

[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 6-10wt.%, Al: 1-6wt.%, Zn: 1-6wt.%, Gd: 0.2-1wt.%, Y: 0.1-1wt.%, Ca: 0.1-1wt.%, total amount of ceramic particles (CP): 0.05-1wt.%,

[0007] Furthermore, the ceramic particles are TiB 2 、TiC、B 4 C and Al 2 O 3 One or more of .

[0008] Furthermore, the average particle size of the ceramic particles is 100 nm-3 μm.

[0009] Furthermore, the high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy has a tensile strength of 320-380 MPa, a yield strength of 300-360 MPa, and an elongation of 8%-15%.

[0010] Another object of the present invention is to disclose a preparation process of a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, which optimizes the composite deformation process parameters, regulates the hard rare earth phase and the nano-reinforcement phase, enhances the dislocation density and texture strength, and greatly improves the strength and plasticity of the dual-phase magnesium-lithium alloy.

[0011] The preparation process of the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy of the present invention comprises the following steps:

[0012] S1. Weigh the raw materials according to mass fraction: pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-Gd master alloy, Mg-Y master alloy and ceramic particles, and pretreat the raw materials;

[0013] S2. placing the raw materials in a high vacuum electromagnetic induction melting furnace equipped with mechanical stirring and / or ultrasonic stirring and a mold heating device to melt the dual-phase magnesium-lithium alloy ingot;

[0014] S3. The dual-phase magnesium-lithium alloy ingot is subjected to homogenization heat treatment, and solution quenching treatment is performed immediately after the homogenization heat treatment is completed;

[0015] S4. isothermally pre-forging the dual-phase magnesium-lithium alloy;

[0016] S5. Rapidly reverse-extrude the dual-phase magnesium-lithium alloy at a variable temperature;

[0017] S6. The dual-phase magnesium-lithium alloy is asynchronously rolled at room temperature to prepare a high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy, also known as a high-strength and toughness micro- and nano-particle-reinforced dual-phase magnesium-lithium alloy.

[0018] Furthermore, the ceramic particles in step S1 are TiB 2 、TiC、B 4 C and Al 2 O 3 One or more of .

[0019] Furthermore, in step S1, the average particle size of the ceramic particles is 100 nm-3 μm.

[0020] Furthermore, in step S1, the purity of the raw materials and the aluminum foil is greater than or equal to 99.99wt.%, and the total impurity content is less than 0.02wt.%.

[0021] Furthermore, the Gd content in the Mg-Gd master alloy is 10-30%, and the Y content in the Mg-Y master alloy is 10-30%.

[0022] Furthermore, the raw material pretreatment method in step S1 is: placing the pure Li ingot in an acetone solution for cleaning and degreasing, polishing the surface of the remaining raw materials to remove the oxide scale, and then placing all the raw materials in a vacuum drying oven for drying.

[0023] Furthermore, the raw material pretreated in step S1 is wrapped with aluminum foil for vacuum storage.

[0024] Furthermore, the smelting process in step S2 is as follows: placing the raw materials in a crucible, turning on the vacuum system to evacuate, and backfilling the inert gas 2-4 times for washing during the evacuation process until the vacuum is 1×10 -2 When the temperature is below Pa, recharge 2-4×10 4 Pa inert gas protects the smelting process; start the circulating water cooling system and heating system, raise the smelting temperature to 720-760℃, keep warm for 10-20min, carry out the first mechanical stirring, start the mold heating device to preheat the mold; reduce the temperature to 700-720℃, carry out ultrasonic treatment, keep warm for 10-20min, carry out the second mechanical stirring, let it stand for 2-5min and then cast; cool to 150-200℃ with the furnace, take out the ingot, and air-cool it in a ventilated place.

[0025] Furthermore, the inert gas in step S2 is high-purity argon.

[0026] Furthermore, in step S2, the mechanical stirring speed is 200-500 r / min, and the time is 2-5 min; the ultrasonic stirring power is 200-260 W, and the time is 1-3 min.

[0027] Furthermore, the casting mold in step S2 is a copper mold, and the mold preheating temperature is 180-280°C.

[0028] Furthermore, the homogenization process in step S3 adopts a medium-temperature box-type resistance furnace.

[0029] Furthermore, in step S3, the homogenization treatment temperature is 240-260° C., the time is 3-8 hours, and the air cooling treatment is performed.

[0030] Furthermore, the solution treatment temperature in step S3 is 350-380° C. for 4-6 hours, and water quenching is performed immediately after completion.

[0031] Furthermore, the isothermal pre-forging process in step S4 is: pre-forging 3-6 times, the forging temperature is 260-300°C, the deformation amount of a single pass is 15-30%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenched.

[0032] Furthermore, the variable temperature rapid reverse extrusion process in step S5: the reverse extrusion is performed in 2 passes, the temperature of the first pass is 300-350°C, the extrusion ratio is 4:1-16:1, the extrusion speed is 9-15m / min, the temperature of the second pass is 250-300°C, the extrusion ratio is 25:1-45:1, the extrusion speed is 4-8m / min, and water quenching is performed immediately after each pass.

[0033] Furthermore, in step S6, the temperature of the asynchronous rolling at room temperature is 20-40° C., the speed ratio of the upper and lower rollers is 1.1:1-1.3:1, the deformation amount of a single pass is 6-15%, and the total deformation amount is 50-70%.

[0034] Another object of the present invention is to disclose a high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy for use in the fields of aerospace and rail transportation.

[0035] The present invention coordinates the content of grain refining elements and ceramic particle grain refiners to synergistically refine the grains of the dual-phase magnesium-lithium alloy, promotes dynamic recrystallization and coordinates the two-phase deformation by optimizing the composite deformation process parameters, and achieves a coordinated improvement in the strength and plasticity of the magnesium-lithium alloy. Specifically, the high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy of the present invention, its preparation process and use have the following advantages compared with the prior art:

[0036] 1) The present invention realizes the synergistic improvement of the strength and plasticity of the dual-phase magnesium-lithium alloy by combining the addition of micro / nano ceramic particles with plastic deformation. On the basis of the grain refinement of rare earth elements and Ca elements, the magnesium-lithium alloy of the present invention introduces micro / nano ceramic particles with good wettability with the Mg matrix, which are adsorbed on the atoms or molecular clusters of the melt to form stable nucleation points, reduce the energy required for nucleation, thereby increasing the number of grain nucleation, and obtaining fine grains during the solidification process. On the other hand, during the solidification process, ceramic particles that have not become heterogeneous nucleation points will be distributed at the front of the solidification interface, hindering the migration of grain boundaries and inhibiting grain growth, thereby obtaining a further refined solidification structure. Fine solidified structures can be inherited to the subsequent plastic deformation process. Pre-forging in the early stage of the plastic deformation process can effectively close the defects of the cast structure and accumulate deformation energy for the subsequent plastic deformation. The first high-temperature, fast and low-deformation reverse extrusion can effectively reduce internal stress and structural heterogeneity and improve plastic deformation capacity. The second high-deformation reverse extrusion deformation can mechanically break the α-Mg phase and promote dynamic recrystallization and precipitation of nano-strengthening phase in the β-Li phase. Water quenching can stabilize the strengthening phase and prevent the growth of the deformed structure. The final room temperature asynchronous rolling process can effectively increase the local shear force, greatly improve the work hardening and particle strengthening effects, and significantly improve the strong plasticity.

[0037] 2) Compared with the traditional dual-phase magnesium-lithium alloy preparation process, the present invention adopts the method of adding alloying elements and ceramic particles in combination, which overcomes the limitations of traditional alloying element design to improve strength and plasticity, and refines the dual-phase magnesium-lithium alloy grains by multiple mechanisms. In addition, the strengthening effect of micro / nano ceramic particles is enhanced by the composite deformation process, and the hard rare earth strengthening phase (Al 2 Y.Al 2 Gd) and Al 2 The size and distribution of the Ca phase improve the dislocation density and texture strength, greatly reduce the plastic loss caused by traditional deformation, and achieve a synergistic improvement in strength and plasticity.

[0038] 3) The tensile strength of the dual-phase magnesium-lithium alloy prepared by the preparation process of the present invention is 320-380 MPa, the yield strength is 300-360 MPa, and the elongation is 8%-15%, which can meet the performance indicators of structural parts in the military and aerospace fields.

[0039] 4) The high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy of the present invention has a simple preparation process and a short flow, and can be suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a process flow chart for preparing the high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0042] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0043] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0044] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0045] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0046] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0047] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0048] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0049] In order to make the technical problems and beneficial effects solved by the preparation method of the present invention clearer, the embodiments of the present invention are further described in detail. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0050] Embodiment 1:

[0051] This embodiment discloses a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.05%, of which TiB 2 The average particle size of the particles is 200 nm.

[0052] The preparation process of the high-strength and toughness particle reinforced dual-phase magnesium-lithium alloy comprises the following steps:

[0053] S1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd, Mg-20Ca master alloy and ceramic particles according to mass fraction. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0054] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4 Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0055] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0056] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0057] S5. The forged dual-phase magnesium-lithium alloy is subjected to two back-extrusion passes, the first pass temperature is 320°C, the extrusion ratio is 9:1, the extrusion speed is 12m / min, the second pass temperature is 260°C, the extrusion ratio is 32:1, the extrusion speed is 6m / min, and water quenching is performed immediately after each pass.

[0058] S6. The extruded dual-phase magnesium-lithium alloy is subjected to room temperature asynchronous rolling, the temperature of the room temperature asynchronous rolling is 25° C., the speed ratio of the upper and lower rollers is 1.2:1, the single-pass deformation is 10%, and the total deformation is 60%.

[0059] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Example 1 was 365 MPa, the yield strength was 349 MPa, and the elongation was 13.1%.

[0060] Embodiment 2:

[0061] This embodiment discloses a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.2%, TiB 2 The average particle size of the particles is 200 nm.

[0062] The preparation process of the high-strength and toughness particle reinforced dual-phase magnesium-lithium alloy comprises the following steps:

[0063] S1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd, Mg-20Ca master alloy and ceramic particles according to mass fraction. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0064] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4 Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0065] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0066] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0067] S5. The forged dual-phase magnesium-lithium alloy is subjected to two back-extrusion passes, the first pass temperature is 320°C, the extrusion ratio is 9:1, the extrusion speed is 12m / min, the second pass temperature is 260°C, the extrusion ratio is 32:1, the extrusion speed is 6m / min, and water quenching is performed immediately after each pass.

[0068] S6. The extruded dual-phase magnesium-lithium alloy is subjected to room temperature asynchronous rolling, the temperature of the room temperature asynchronous rolling is 25° C., the speed ratio of the upper and lower rollers is 1.2:1, the single-pass deformation is 10%, and the total deformation is 60%.

[0069] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Example 2 was 347 MPa, the yield strength was 323 MPa, and the elongation was 11.2%.

[0070] Embodiment 3:

[0071] This embodiment discloses a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.5%, TiB 2 The average particle size of the particles is 200 nm.

[0072] The preparation process of the high-strength and toughness particle reinforced dual-phase magnesium-lithium alloy comprises the following steps:

[0073] S1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd, Mg-20Ca master alloy and ceramic particles according to mass fraction. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0074] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0075] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0076] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0077] S5. The forged dual-phase magnesium-lithium alloy is subjected to two back-extrusion passes, the first pass temperature is 320°C, the extrusion ratio is 9:1, the extrusion speed is 12m / min, the second pass temperature is 260°C, the extrusion ratio is 32:1, the extrusion speed is 6m / min, and water quenching is performed immediately after each pass.

[0078] S6. The extruded dual-phase magnesium-lithium alloy is subjected to room temperature asynchronous rolling, the temperature of the room temperature asynchronous rolling is 25° C., the speed ratio of the upper and lower rollers is 1.2:1, the single-pass deformation is 10%, and the total deformation is 60%.

[0079] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Example 2 was 339 MPa, the yield strength was 317 MPa, and the elongation was 8.2%.

[0080] Embodiment 4:

[0081] This embodiment discloses a high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.05%, TiB 2 The average particle size of the particles was 2 μm.

[0082] The preparation process of the high-strength and toughness particle reinforced dual-phase magnesium-lithium alloy comprises the following steps:

[0083] S1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd, Mg-20Ca master alloy and ceramic particles according to mass fraction. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0084] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4 Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0085] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0086] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0087] S5. The forged dual-phase magnesium-lithium alloy is subjected to two back-extrusion passes, the first pass temperature is 320°C, the extrusion ratio is 9:1, the extrusion speed is 12m / min, the second pass temperature is 260°C, the extrusion ratio is 32:1, the extrusion speed is 6m / min, and water quenching is performed immediately after each pass.

[0088] S6. The extruded dual-phase magnesium-lithium alloy is subjected to room temperature asynchronous rolling, the temperature of the room temperature asynchronous rolling is 25° C., the speed ratio of the upper and lower rollers is 1.2:1, the single-pass deformation is 10%, and the total deformation is 60%.

[0089] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Example 4 was 351 MPa, the yield strength was 331 MPa, and the elongation was 11.8%.

[0090] Comparative Example 1:

[0091] This comparative example discloses a dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8 wt.%, Al: 3 wt.%, Zn: 2 wt.%, Y: 0.3 wt.%, Gd: 0.2 wt.%, Ca: 0.3 wt.%.

[0092] The preparation process of the dual-phase magnesium-lithium alloy comprises the following steps:

[0093] S1. The composition and mass fraction of each element of the dual-phase magnesium-lithium alloy are as follows: the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd and Mg-20Ca master alloy are weighed according to the mass fraction, and the purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0094] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4 Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0095] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0096] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0097] S5. The forged dual-phase magnesium-lithium alloy is subjected to two back-extrusion passes, the first pass temperature is 320°C, the extrusion ratio is 9:1, the extrusion speed is 12m / min, the second pass temperature is 260°C, the extrusion ratio is 32:1, the extrusion speed is 6m / min, and water quenching is performed immediately after each pass.

[0098] S6. The extruded dual-phase magnesium-lithium alloy is subjected to room temperature asynchronous rolling, the temperature of the room temperature asynchronous rolling is 25° C., the speed ratio of the upper and lower rollers is 1.2:1, the single-pass deformation is 10%, and the total deformation is 60%.

[0099] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Comparative Example 1 was 334 MPa, the yield strength was 313 MPa, and the elongation was 14.9%.

[0100] Comparative Example 2:

[0101] This comparative example discloses a dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.05%, TiB 2 The average particle size of the particles is 200 nm.

[0102] The preparation process of the dual-phase magnesium-lithium alloy comprises the following steps:

[0103] S1. Weigh the raw materials pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-20Y, Mg-20Gd, Mg-20Ca master alloy and ceramic particles according to mass fraction. The purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, and the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0104] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0105] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0106] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0107] S5. The forged dual-phase magnesium-lithium alloy is forward extruded with an extrusion ratio of 32:1 and an extrusion speed of 6 m / min.

[0108] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Comparative Example 2 was 301 MPa, the yield strength was 276 MPa, and the elongation was 15.3%.

[0109] Comparative Example 3:

[0110] This comparative example discloses a dual-phase magnesium-lithium alloy, comprising the following components and contents: Li: 8wt.%, Al: 3wt.%, Zn: 2wt.%, Y: 0.3wt.%, Gd: 0.2wt.%, Ca: 0.3wt.%, TiB 2 :0.05%, TiB 2 The average particle size of the particles is 200 nm.

[0111] The preparation process of the dual-phase magnesium-lithium alloy comprises the following steps: S1. weighing raw materials pure Mg ingots, pure Li ingots, pure Al ingots, pure Zn ingots, Mg-20Y, Mg-20Gd, Mg-20Ca master alloys and ceramic particles according to mass fraction, the purity of the raw materials is 99.99wt.%, and the total impurity content is less than 0.01wt.%. The pure Li ingot is placed in an acetone solution for cleaning and degreasing, the surface of the remaining raw materials is polished to remove the oxide scale, and then all the raw materials are placed in a vacuum drying oven for drying.

[0112] S2. Put all raw materials into the crucible, turn on the vacuum system to evacuate, and backfill with inert gas 3 times during the evacuation process to purge the air until the vacuum reaches 6×10 -3 Pa and then charge 3×10 4 Pa inert gas protects the smelting process. Turn on the circulating water cooling system and heating system, raise the smelting temperature to 740℃, keep warm for 10 minutes, carry out the first mechanical stirring, the mechanical stirring speed is 450r / min, the time is 2min, keep warm again for 10min, carry out ultrasonic treatment, the ultrasonic treatment power is 240W, the time is 2min, start the mold heating device, preheat the mold to 240℃. Reduce to 710℃, keep warm for 10min, carry out the second mechanical stirring, let it stand for 3min before casting. Cool down to 160℃ with the furnace, take out the ingot, and air cool it in a ventilated place.

[0113] S3. The dual-phase magnesium-lithium alloy ingot is placed in a resistance furnace for homogenization heat treatment at 260°C for 5 h and solution treatment at 350°C for 4 h, followed by water quenching.

[0114] S4. The two-phase magnesium-lithium alloy after solid solution is pre-forged for three times, the forging temperature is 280°C, the deformation amount of a single pass is 20%, the first pass is upsetting along the axial direction of the ingot; the second pass is drawing along the length direction of the ingot; the third pass is rotating 90° along the length direction for secondary drawing; three passes constitute a cycle, one fire pass is completed and immediately water quenching is performed.

[0115] S5. The extruded dual-phase magnesium-lithium alloy is rolled at room temperature, the temperature of the room temperature rolling is 25° C., the deformation amount of a single pass is 5%, and the total deformation amount is 40%.

[0116] Through the tensile property test, it was obtained that the tensile strength of the dual-phase magnesium-lithium alloy in Comparative Example 3 was 312 MPa, the yield strength was 288 MPa, and the elongation was 9.3%.

[0117] Table 1 Strength and elongation of dual-phase magnesium-lithium alloy in the examples and comparative examples

[0118]

[0119] It can be seen from the strength and plasticity comparison of Examples 1-3 in Table 1 that with the increase in the content of nano-ceramic particles, the strength and plasticity of the dual-phase magnesium-lithium alloy decrease. This is because the excessive content of ceramic particles can easily produce local stress concentration during the deformation process, reducing the strength and plasticity. According to the strength and plasticity results of Examples 1 and 4, the fine particle size can further improve the strength and plasticity. Nanoparticles have a higher specific surface area, which increases the barrier effect on dislocations and improves performance. Compared with Example 1, after adding ceramic particles, Example 1 can improve the performance strength by up to 31MPa, while the plasticity only decreases by 1.8%; compared with the pre-forged positive extrusion of Example 2, the strength is increased by 64MPa, and the plasticity has no obvious decrease; and compared with the pre-forged room temperature rolling of Example 3, the strength of the dual-phase magnesium-lithium alloy after the composite deformation process of the present invention is increased by 53MPa, and the plasticity is increased by 3.8%, and the strength and plasticity are significantly improved.

[0120] In summary, the preparation process provided by the present invention can greatly enhance the strengthening effect of plastic deformation and achieve a synergistic improvement in strength and plasticity.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy, characterized in that: The components and contents included are: Li: 6-10wt.%, Al: 1-6wt.%, Zn: 1-6wt.%, Gd: 0.2-1wt.%, Y: 0.1-1wt.%, Ca: 0.1-1wt.%, total amount of ceramic particles: 0.05-1wt.%.

2. The high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 1, characterized in that: The ceramic particles are one or more of TiB2, TiC, B4C and Al2O3; And / or, the average particle size of the ceramic particles is 100 nm-3 μm.

3. A process for preparing the high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy according to claim 1 or 2, characterized in that: The following steps are involved: S1. Weigh the raw materials according to mass fraction: pure Mg ingot, pure Li ingot, pure Al ingot, pure Zn ingot, Mg-Gd master alloy, Mg-Y master alloy and ceramic particles, and pretreat the raw materials; S2. placing the raw materials in a high vacuum electromagnetic induction melting furnace equipped with mechanical stirring and / or ultrasonic stirring and a mold heating device to melt the dual-phase magnesium-lithium alloy ingot; S3. The dual-phase magnesium-lithium alloy ingot is subjected to homogenization heat treatment, and solution quenching treatment is performed immediately after the homogenization heat treatment is completed; S4. isothermally pre-forging the dual-phase magnesium-lithium alloy; S5. Rapidly reverse-extrude the dual-phase magnesium-lithium alloy at a variable temperature; S6. The dual-phase magnesium-lithium alloy is asynchronously rolled at room temperature to prepare a high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy.

4. The preparation process of the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The ceramic particles in step S1 are one or more of TiB2, TiC, B4C and Al2O3; And / or, the average particle size of the ceramic particles in step S1 is 100 nm-3 μm; And / or, the purity of the raw materials and the aluminum foil in step S1 is greater than or equal to 99.99wt.%, and the total impurity content is less than 0.02wt.%; And / or, the Gd content in the Mg-Gd master alloy is 10-30%, and the Y content in the Mg-Y master alloy is 10-30%; And / or, the raw material pretreatment method in step S1 is: placing the pure Li ingot in an acetone solution to clean and remove oil, grinding the surface of the remaining raw materials to remove oxide scale, and then placing all the raw materials in a vacuum drying oven for drying; And / or, the raw material pretreated in step S1 is wrapped with aluminum foil for vacuum storage.

5. The preparation process of the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The smelting process in step S2 is as follows: the raw materials are placed in a crucible, the vacuum system is turned on to evacuate, and the inert gas is repeatedly backfilled for washing during the evacuation process to a high vacuum of 1×10 -2 When the temperature is below Pa, recharge 2-4×10 4 Pa inert gas is used to protect the smelting process; the circulating water cooling system and heating system are turned on, the smelting temperature is raised to 720-760℃, and after keeping warm for 10-20 minutes, the first mechanical stirring is carried out, and the mold heating device is started to preheat the mold; the temperature is reduced to 700-720℃, ultrasonic treatment is carried out, and the temperature is kept warm for 10-20 minutes, and the second mechanical stirring is carried out. After standing for 2-5 minutes, casting is performed; the ingot is taken out after cooling to 150-200℃ with the furnace, and air-cooling is carried out in a ventilated place; and / or, the inert gas is high purity argon; and / or, the mechanical stirring speed is 200-500 r / min, the time is 2-5 min; the ultrasonic stirring power is 200-260 W, the time is 1-3 min; And / or, the casting mold is a copper mold, and the mold preheating temperature is 180-280°C.

6. The process for preparing the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The homogenization process in step S3 is performed using a medium temperature box-type resistance furnace; And / or, the homogenization treatment temperature in step S3 is 240-260°C, the time is 3-8h, and the air cooling treatment is performed; And / or, the solution treatment temperature in step S3 is 350-380° C., the time is 4-6 hours, and water quenching is performed immediately after completion.

7. The process for preparing the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The isothermal pre-forging process in step S4 is as follows: pre-forging 3-6 times, the forging temperature is 260-300°C, the deformation of a single time is 15-30%, the first time is upsetting along the axial direction of the ingot; the second time is drawing along the length direction of the ingot; the third time is rotating 90° along the length direction for secondary drawing; three times constitute a cycle, one fire pass is completed and immediately water quenched.

8. The process for preparing the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The variable temperature rapid reverse extrusion process in step S5: reverse extrusion is performed in two passes, the temperature of the first pass is 300-350°C, the extrusion ratio is 4:1-16:1, the extrusion speed is 9-15m / min, the temperature of the second pass is 250-300°C, the extrusion ratio is 25:1-45:1, the extrusion speed is 4-8m / min, and water quenching is performed immediately after each pass.

9. The process for preparing the high-strength and tough particle-reinforced dual-phase magnesium-lithium alloy according to claim 3, characterized in that: The temperature of the room temperature asynchronous rolling in step S6 is 20-40° C., the speed ratio of the upper and lower rollers is 1.1:1-1.3:1, the deformation amount of a single pass is 6-15%, and the total deformation amount is 50-70%.

10. Use of the high-strength and toughness particle-reinforced dual-phase magnesium-lithium alloy according to claim 1 or 2 in the fields of aerospace and rail transportation.

Citation Information

Patent Citations

  • A method for preparing micro / nano-scale TiB2 particle-reinforced magnesium-lithium based composite materials

    CN111304506B